Analisis Proses Pembelajaran pada Mata Pelajaran Prakarya - Chery Yan Anugrah; Merrisa Monoarfa (Universitas Negeri Makassar, 2023)
This study aims to describe the learning process for Prakarya subjects at UPTD SMPN 4 Bantimurung. This study is a qualitative research with the type of research is simple descriptive qualitative. This research was conducted at UPTD SMPN 4 Bantimurung class VIII (A), (B), and (C) in the odd semester of the 2022/2023 academic year. Collecting data using observation guidelines, interview, and documentation. This research was conducted by self-determining the research subjects through the criteria. Data analysis methods consist of data collection, data reduction, data presentation, and drawing conclusions. Based on the results, it was found that Prakarya learning process at UPTD SMPN 4 Bantimurung was carried out using a questions and answer, practice learning model, learning took place with the teacher reflecting back on the previous meeting material, explaining or dictating learning material, learning practices and giving assignments directly. The form of evaluation is carried out by the teacher by giving assignments both in printed books and questions directly by the teacher, asking questions at the end of learning. Obstacles during the learning process that the lack of adequate tools and materials for implementing learning practices, the use of learning videos is the solution.